General Seizures Due to Brain Abscess Causa Suspected Intracranial Tuberculosis at Prof Aloei Saboe Hospital Gorontalo - Winansih Gubali; Dian Suciaty Annisa (Universitas Negeri Gorontalo, 2022)
Introduction: Seizures are a severe clinical condition with complications of brain abscess. This report will describe the rare occurrence of generalized seizures due to Mycobacterium tuberculosis (MTB) brain abscess.Case: Male, 57 years old, admitted to the emergency department with two episodes of generalized seizures one hour before admission. The patient had a history of pulmonary tuberculosis during four months of treatment and was treated with an anti-tuberculosis fixed drug combination (FDC) 3. The patient was in a state of delirium and had lower extremity weakness. The chest radiograph shows a multifocal patchy opacity in the right upper lobe with thickening in the right pericardium. Pre-Contrast MSCT-Scan of the brain showed multiple hypodense lesions in the left frontal lobe, right frontoparietal, left basal ganglia, and pons. Post-contrast shows multiple low-attenuation, oval-shaped lesions with peripheral enhancement (double rim sign) with vasogenic edema. Finally, the patient was diagnosed with a tuberculous brain abscess.Discussion: CNS tuberculosis is a rare cause of seizures and is often followed by a history of pulmonary tuberculosis. Tuberculosis appears on the Contrast MSCT Scan Brain as an avascular mass lesion of low density and sometimes more significant than expected around cerebral edema. End-stage tuberculosis is well encapsulated and has peripheral ring enhancement with vasogenic edema.Conclusion: Pre-Post Contrast Brain MSCT is the diagnostic imaging of choice for suspected tuberculous brain abscess.